ChemInform Abstract: The First Tetradentate μ‐1ϰ2:2ϰ2‐Sn2Se6 Ligand to a Lanthanide(III) Center: Solvothermal Syntheses and Characterizations of Lanthanide Selenidostannate Polymers with Tetraethylenepentamine as a Second Ligand. Issue 4 (31st January 2013) - Tang, Weiwei; Chen, Ruihong; Jiang, Wenqing; Zhang, Yong; Jia, Dingxian
Abstract Compounds (IV) and (VIII) crystallize in the monoclinic space group C2/c with Z = 4.